Correlation Between Anxiety Scores and Tuak Drink Consumption Scores in Batak Tuak Drinker: Symptom of Anxiety in Batak Tuak Drinker (International Journal of Scientific Research and Management (IJSRM), 2021)
Background : In Indonesia, particularly among Bataknees men in Medan, tuak has been known as a staple, enjoyed by mostly men to strengthen their brotherhood. Concurrent Anxiety Disorders and Alcohol Use Disorders (AUD) are relatively common and closely related to the presentation of complex clinical symptoms that warrant an appropriate diagnosis and treatment. Method : Sixty tuak drinkers from 4 districts of Medan were recruited by using a cluster sampling method. Participants aged 25-55 years old with inclusion criteria were Batak men who drank Tuak, minimum education by completing junior high school and history of drinking tuak took less than 12 months, and AUDIT cutoff value less than or equal to 7. This study’s exclusion criteria were no history of psychiatric and general health disorders in the subject. Result : The results of this study found a significant relationship between the HADS-A score and the AUDIT total score. Also found a significant relationship between the drinking frequency score, the drinking quantity score, the frequency score of heavy drinking, and the HADS-A score. Conclusion : The results of this study are essential evidence to promote mental health in the future, especially in the city of Medan.